Strengthening Teacher Capacity in Bihar through ICT : Designing Innovative Solution to Unique Challenges - World Bank (Washington, DC, 2014)
Within this context, there are significant opportunities to harness Information and Communication Technology (ICT) and Open and Distance Learning (ODL) in teacher education, especially to deliver pre-service teacher education. Consequently, the Government of Bihar requested the World Bank to provide support in development of distance education curriculum, related syllabi, content, effective delivery mechanisms, appropriate student support systems, and assessment strategies to meet the needs of its untrained teachers. Many other states and countries are facing similar problems, and will need to prepare comprehensive time-bound plans for untrained teachers to acquire the prescribed qualifications (both academic and professional). Thus, experiences in Bihar might provide models for developing an ICT-based teacher education system that can be used as a useful reference point by others facing similar problems. This report outlines these experiences and shares lessons learned through the process to date.